2014
DOI: 10.1104/pp.114.236737
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Fungal Effector Lipase Releases Free Fatty Acids to Inhibit Innate Immunity-Related Callose Formation during Wheat Head Infection  

Abstract: The deposition of the (1,3)-b-glucan cell wall polymer callose at sites of attempted penetration is a common plant defense response to intruding pathogens and part of the plant's innate immunity. Infection of the Fusarium graminearum disruption mutant Dfgl1, which lacks the effector lipase FGL1, is restricted to inoculated wheat (Triticum aestivum) spikelets, whereas the wild-type strain colonized the whole wheat spike. Our studies here were aimed at analyzing the role of FGL1 in establishing full F. graminear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 52 publications
(68 reference statements)
1
103
0
Order By: Relevance
“…Several RLCKs are thought to play pivotal roles in plant defense (Martin et al, 1994;Swiderski and Innes, 2001;Zhang et al, 2010;Shi et al, 2013;Liu et al, 2011;Feng et al, 2012;Shinya et al, 2014;Yamaguchi et al, 2013;Dubouzet et al, 2011;Wang et al, 2015b;Zhou et al, 2016) and are thought to be involved in connecting signal perception by RLKs in the plasma membrane to downstream intracellular signal transduction systems. Callose synthases such as LOC_Os01g67364.1 perform callose biosynthesis in plants (Xie et al, 2011), and there is considerable evidence that they function in preventing penetration by herbivores (Enrique et al, 2011;Blümke et al, 2013Blümke et al, , 2014Ellinger et al, 2013). We found that the promoters of RLCK281 and LOC_Os01g67364.1 were associated with WRKY46 and WRKY72; the presence of the CC, NB, and CN domains or FL BPH14 enhanced the association between the WRKYs and the promoters of RLCK281 and LOC_Os01g67364.1 in rice.…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 75%
“…Several RLCKs are thought to play pivotal roles in plant defense (Martin et al, 1994;Swiderski and Innes, 2001;Zhang et al, 2010;Shi et al, 2013;Liu et al, 2011;Feng et al, 2012;Shinya et al, 2014;Yamaguchi et al, 2013;Dubouzet et al, 2011;Wang et al, 2015b;Zhou et al, 2016) and are thought to be involved in connecting signal perception by RLKs in the plasma membrane to downstream intracellular signal transduction systems. Callose synthases such as LOC_Os01g67364.1 perform callose biosynthesis in plants (Xie et al, 2011), and there is considerable evidence that they function in preventing penetration by herbivores (Enrique et al, 2011;Blümke et al, 2013Blümke et al, , 2014Ellinger et al, 2013). We found that the promoters of RLCK281 and LOC_Os01g67364.1 were associated with WRKY46 and WRKY72; the presence of the CC, NB, and CN domains or FL BPH14 enhanced the association between the WRKYs and the promoters of RLCK281 and LOC_Os01g67364.1 in rice.…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 75%
“…Also, they showed that the highest amount of callose content was seen in the Sumai3 cultivar. Similarly, Blümke et al (2014) reported that linoleic and α-linolenic acid have a major function in the suppression of the innate immunity-related callose biosynthesis and, hence, progress of F. graminearum wheat infection. In plant-pathogen interactions, an oxidative response is an early and complex host reaction to the phytopathogens, which occur in the attacked and neighboring cells of the infection site (Dmochowska--Boguta et al 2013;Taheri et al 2014).…”
Section: Discussionmentioning
confidence: 92%
“…LA plays an important role in wheat and barley in defence against F. graminearum and has been established to be a FHB resistance-related metabolite6723. Higher concentrations of LA accumulate in FHB-resistant wheat lines than in susceptible lines7, which suggests that LA contributes to FHB resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of LA is greater in FHB-resistant wheat lines than in susceptible lines6, suggesting that LA may contribute to FHB resistance. Enhanced accumulation of LA and other free fatty acids can reinforce the cuticle, which acts as a barrier to pathogen entry7. LA is metabolised by linoleate diol synthase (LDS)89 and linoleic acid isomerase (LAI) in fungi (Fig.…”
mentioning
confidence: 99%